PROFIL SKABIES DIPOLIKLINIK KULIT DAN KELAMIN BLU RSUP PROF. DR. R. D. KANDOU MANADO PERIODE JANUARI – DESEMBER 2012 - Gunawan, I Made Erik Sastra; Kandou, Renate T.; Pandaleke, Herry E. J. (Universitas Sam Ratulangi, 2014)
Abstract: Scabies is a skin disease caused by sentization of Sarcoptes scabiei var. hominis and its products. Scabies affects skin and highly contagious in humans and animals, affects all races and classes in all over the world. Risk factors of this disease is low socioeconomic, individual’s poor hygiene, dirty environment, unhealthy behaviour, and high population density. The purpose of this study was to evaluate the profile of scabies patients in Dermatovenereology clinic of Prof. Dr. R. D. Kandou Hospital Manado during the period from January – December 2012. The Method used in this study was descriptive retrospective. The result showed that among 41 scabies patients (3.74%), the highest rate was from age group between 15 – 24 years (29.26%), male (63.41%), most occupation was students (48.78%), most location affected was generalized (80.48%) and most therapy used was anti-scabies combined with antihistamine (60.98%) Keywords: scabies, profile Abstract: Skabies adalah penyakit kulit yang di sebabkan oleh sensitisasi terhadap sarcoptes scabiei varietas hominis dan produknya. Skabies menyerang kulit dan mudah menular dari manusia ke manusia, dari hewan ke manusia atau sebaliknya, dapat mengenai semua ras dan golongan di seluruh dunia. Faktor risiko penyakit ini adalah sosial ekonomi yang rendah, higiene perorangan yang jelek, lingkungan yang tidak bersih, perilaku yang tidak sehat, serta kepadatan penduduk. Tujuan penelitian untuk mengetahui profil pasien skabies di poliklinik Kulit dan Kelamin RSUP Prof. Dr. R. D. Kandou Manado periode Januari – Desember 2012. Metode penelitian ini bersifat deskriptif retrospektif. Hasil penelitian memperlihatkan dari 41 penderita skabies (3,74%) terbanyak dari kelompok umur 15 – 24 tahun (29,26%), jenis kelamin laki – laki (63,41%), pekerjaan sebagai pelajar (48,78%), lokasi secara generalisata (80,48%) dan terapi antiskabies yang di kombinasikan dengan antialergi (60,98%). Kata kunci: skabies, profil